Erlotinib Induced Trichomegaly of the Eyelashes - Jeon, Sang-Hoon (The Korean Academy of Tuberculosis and Respiratory Diseases, 2013)
Epithelial growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) have been widely used for non-small-cell lung cancer patients. Its untoward cutaneous effects are largely well known and developed in many patients treated with EGFR TKIs. However trichomegaly of eyelash is rarely reported. Although trichomegaly is not a drug-limiting side effect, it could be troublesome of continuing the treatment because of cosmetic issue or eyeball irritation by long eyelashes. Therefore clinicians are needed to pay attention to this uncommon effect. We herein describe erlotinib induced trichomegaly of eyelashes in a woman with adenocarcinoma of the lung.